Evaluation-oriented LADM profile and data integration architecture for mass appraisal - Myronov, O. (Land Management, Cadastre and Land Monitoring, 2026)
The article proposes an assessment-oriented national profile of the Land Administration Domain Model for Ukraine, which sets out a unified logic for integrating cadastral, legal, urban planning, and market information in a format suitable for mass assessment and taxation of real estate. The conceptual framework is based on the provisions of ISO 19152-1:2024 and ISO 19152-4:2025, and the subject area is structured in the form of a UML model with the definition of key entities and relationships between spatial units, legal statuses, and valuation results. To transition from disparate registries and cartographic materials to a coordinated “valuation-ready” dataset, an intermediate layer of semantic harmonization is justified, including unified identifiers, classifiers, and attribute normalization rules. A practical scenario for forming an MVP showcase for mass valuation with the fixation of data sources and quality control indicators (completeness of key fields, duplicates, spatial inconsistencies, price outliers) is described. The technological implementation of the profile is supported by an open stack of PostgreSQL/PostGIS, QGIS, and Python, which ensures the reproducibility of calculations, the auditability of decisions, and the possibility of scaling for the needs of communities and government agencies. The proposed approach forms the basis for conducting various types of assessments (regulatory, market, and mass) in a single information loop.Received: 15.12.2025;Accepted: 14.01.2026;
Keywords: LADM; mass appraisal; land registry; data interoperability; CAMA; geospatial data; valuation profile